The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.antiviral.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of host-targeted covalent inhibitors of dengue virus

Abstract: We report here on an approach targeting the host reactive cysteinome to identify inhibitors of host factors required for the infectious cycle of Flaviviruses and other viruses. We used two parallel cellular phenotypic screens to identify a series of covalent inhibitors, exemplified by QL-XII-47, that are active against dengue virus. We show that the compounds effectively block viral protein expression and that this inhibition is associated with repression of downstream processes of the infectious cycle, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…We demonstrated that QL47 inhibits not only flaviviruses but also several unrelated, medically relevant viruses, including poliovirus, Ebola virus, and human orthopneumovirus (6,9,10), consistent with a host-rather than virus-targeting mode of action. Subsequent structure-activity relationship (SAR) studies revealed that QL47's antiviral activity is closely associated with inhibition of steady-state viral protein expression (6,9). We demonstrated that TEC-family kinases such as BMX or BTK, the previously characterized targets of QL47 (8), are not responsible for antiviral activity (9).…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…We demonstrated that QL47 inhibits not only flaviviruses but also several unrelated, medically relevant viruses, including poliovirus, Ebola virus, and human orthopneumovirus (6,9,10), consistent with a host-rather than virus-targeting mode of action. Subsequent structure-activity relationship (SAR) studies revealed that QL47's antiviral activity is closely associated with inhibition of steady-state viral protein expression (6,9). We demonstrated that TEC-family kinases such as BMX or BTK, the previously characterized targets of QL47 (8), are not responsible for antiviral activity (9).…”
mentioning
confidence: 61%
“…We demonstrated that covalent modification of QL47 targets is essential, as replacement of the cysteine-reactive acrylamide moiety with a nonreactive propyl amide yields an inactive compound, QL47R ( Fig. 1A) (6,9). We also identified acrylamide-containing derivatives, such as YKL-04-085 ( Fig.…”
Section: Ql47 Inhibits Viral and Host Protein Synthesismentioning
confidence: 83%
See 3 more Smart Citations